Knowledge of medical students regarding the cariogenic potential of paediatric liquid medications: a cross-sectional study - Laura Marqués-Martínez; Cristina Olano-López; Juan Ignacio Aura-Tormos; Carla Borrell-García; Paula Boo-Gordillo; María Carmona-Santamaría; Clara Guinot-Barona; Esther García-Miralles (BMC Oral Health, 2026)
Abstract Background Paediatric liquid medications may contain sucrose, acidulants, and other formulation characteristics that create a cariogenic and erosive oral environment. This generates a therapeutic paradox: medicines prescribed to restore systemic health may also contribute to preventable dental disease when used frequently or without preventive guidance. Because prevention can begin at the point of prescription, future prescribers’ knowledge of medication excipients is relevant to paediatric oral-health promotion. Methods An observational, descriptive, cross-sectional study was conducted among 114 fifth- and sixth-year medical students at the Universidad Católica de Valencia, Spain. An anonymous structured 10-item questionnaire assessed knowledge of medication composition, dental risk perception, and preventive attitudes. Analyses included descriptive statistics, Pearson’s chi-square test, Friedman test with Wilcoxon post-hoc comparisons, Spearman correlation, and binary logistic regression. Results Most participants perceived paediatric medications as sweet-tasting (93.0%), but 44.7% did not know the main sweetener commonly associated with cariogenic liquid formulations and only 24.6% identified sucrose. A perceived association between liquid medications and dental alterations was reported by 71.1% of students, more frequently by women in univariate analysis. In multivariable analysis, composition knowledge was the only independent predictor of dental risk perception (OR = 2.84; 95% CI 1.16–6.93; p = 0.022). Drug and disease characteristics were prioritised in prescribing decisions, whereas oral-health consequences were not explicitly represented within the assessed prescribing-priority framework. Conclusions Future prescribers showed a relevant gap in knowledge of the cariogenic composition of paediatric liquid medications. Integrating concise, prescribing-focused oral-health content into medical curricula may improve risk recognition and support interdisciplinary prevention of medication-associated dental disease.